2010
DOI: 10.1253/circj.cj-09-0846
|View full text |Cite
|
Sign up to set email alerts
|

Single-Site Bachmann's Bundle Pacing Is Beneficial While Coronary Sinus Pacing Results in Echocardiographic Right Heart Pacemaker Syndrome in Brady-Tachycardia Patients

Abstract: Background: It has been proposed that multisite atrial pacing (MSAp) restores atrial electrical activation and prevents atrial fibrillation recurrence; however, single-site Bachmann's bundle pacing (BBp) has also been reported as providing effective atrial resynchronization. Coronary sinus pacing (CSp) leads to reversed impulse propagation within the atria. Methods and Results:Acute echocardiographic examination was performed in 15 healthy subjects, and in 25 patients with sinus node dysfunction and recurrent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 25 publications
1
14
0
Order By: Relevance
“…Pacing at BBR was associated with preexcitation of LA anterior sites and reduced the mean and total time to activate the LA compared to SN and RAA pacing. This resulted in near‐simultaneous completion of RA and LA activation and was associated with the shortest observed global atrial activation time of all pacing configurations, congruent with prior studies that have suggested that BBR pacing affords electromechanical activation synchrony as determined by echocardiographic assessment of mean and total biatrial activation times . However, disparate activation at BBR and CSO was associated with increased LA activation dispersion more so than with SN or RAA pacing, which shifted the site of latest activation to the POST LA, and was associated with prolonged intra‐LA activation (P = 0.02 vs. SN).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Pacing at BBR was associated with preexcitation of LA anterior sites and reduced the mean and total time to activate the LA compared to SN and RAA pacing. This resulted in near‐simultaneous completion of RA and LA activation and was associated with the shortest observed global atrial activation time of all pacing configurations, congruent with prior studies that have suggested that BBR pacing affords electromechanical activation synchrony as determined by echocardiographic assessment of mean and total biatrial activation times . However, disparate activation at BBR and CSO was associated with increased LA activation dispersion more so than with SN or RAA pacing, which shifted the site of latest activation to the POST LA, and was associated with prolonged intra‐LA activation (P = 0.02 vs. SN).…”
Section: Discussionsupporting
confidence: 83%
“…Right atrial appendage (RAA) pacing is employed clinically to treat SN dysfunction and suppress AF, but may further aggravate the atrial physiology that underlies these conditions and may worsen atrial dyssynchrony . Pacing the interatrial septum and at Bachmann's bundle (BBR) have been advocated to achieve or maintain atrial synchrony and prevent atrial fibrillation; however, clinical studies have not consistently demonstrated superiority of an alternate pacing location …”
Section: Introductionmentioning
confidence: 99%
“…We believe our study provides the grounds for testing this hypothesis in clinical settings, as this may lead to further improvements in assessing patient suitability for atrial septal pacing. Recently, Dabrowska-Kugacka et al 47 reported that single-site BB pacing resulted in restoring atrial contraction synchrony, whereas CS pacing resulted in reduced RA filling, shortened mechanical atrioventricular delay in the right heart, and reduced right ventricular inflow, thus inducing echocardiographic pacemaker syndrome in the right heart. However, pacemaker syndrome has not been reported in any previous studies involving permanent CSo pacing.…”
Section: Discussionmentioning
confidence: 99%
“… 17 , 18 On the contrary, Kugacka et al have shown that single site CS pacing causes echocardiographic pacemaker syndrome in the right heart because of simultaneous retardation of RA contraction and earlier ventricular activation, while single sit BB pacing provides the best atrial contraction synchrony in patients with ACD, and has a comparable effect on global function to multisite atrial septal pacing. 19 However, Choudhuri et al have suggested that in patients with intra-atrial conduction delay get most benefits from lower atrial septal pacing whereas patients with interatrial conduction delay require pacing at the region of BB. 20 A Report of the American College of Cardiology Foundation/American Heart Association Task Force on Practice Guidelines and the Heart Rhythm Society in 2012 stated that dual-site right atrial pacing or alternate single-site atrial pacing from unconventional sites (e.g., atrial septum or Bachmann’s bundle) may offer additional benefits to single-site right atrial pacing from the appendage in patients with symptomatic drug-refractory AF and concomitant bradyarrhythmias; however, results from these studies are also contradictory and inconclusive.…”
Section: Status Of Alternate Site Atrial Pacingmentioning
confidence: 99%